2000
DOI: 10.1007/s002210000541
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the cortical silent period after repetitive magnetic stimulation of cortical motor areas

Abstract: The physiological mechanisms underlying the lengthening of the silent period (SP) evoked in active upper limb muscles by repetitive transcranial magnetic stimulation (rTMS) of the motor areas were studied in normal subjects. rTMS was delivered at frequencies of 1 Hz, 2 Hz, 3 Hz, 5 Hz, 10 Hz and 15 Hz and at an intensity just above the motor threshold (Mth). Trains delivered at 2 Hz, 3 Hz, 5 Hz, 10 Hz and 15 Hz significantly prolonged the cortical SP, whereas stimuli at 1 Hz did not. The first few stimuli in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 3 publications
8
34
2
1
Order By: Relevance
“…In an earlier study, we observed that in normal subjects rTMS delivered at frequencies of 3 and 5 Hz prolongs the duration of the SP and probably does so by altering the activity of the cortical inhibitory interneurons. 10,11 Here we now show that rTMS prolongs the cortical SP to a similar extent, also in patients with PD. The normal pattern of cortical SPs during rTMS in PD suggests that the cortical inhibitory interneurons mediating the SP as tested by rTMS function normally.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In an earlier study, we observed that in normal subjects rTMS delivered at frequencies of 3 and 5 Hz prolongs the duration of the SP and probably does so by altering the activity of the cortical inhibitory interneurons. 10,11 Here we now show that rTMS prolongs the cortical SP to a similar extent, also in patients with PD. The normal pattern of cortical SPs during rTMS in PD suggests that the cortical inhibitory interneurons mediating the SP as tested by rTMS function normally.…”
Section: Discussionmentioning
confidence: 73%
“…9 Besides altering the MEPs, trains of rTMS prolong the duration of the cortical SP evoked by magnetic stimuli. 10,11 Repetitive stimu-lation of the motor cortex therefore influences the activity of excitatory as well as inhibitory neural elements of cortical motor areas. We investigated the effects of rTMS on MEPs and cortical SPs in patients with PD.…”
mentioning
confidence: 99%
“…No obvious association is apparent between either (1) intensity of single-frequency rTMS and effect or (2) number of rTMS stimuli and effect (Table 3). However, there is some suggestion from data of the effects of stimulation at 3 Hz and 5 Hz that prolongation of the silent period might be related to the number of stimuli given at the same intensity 27,46 (Table 4). The effects of combined-frequency rTMS on MEP amplitude were mostly inhibitory 33,34 or had no effect 33 using the parameters tested ( Table 6).…”
Section: Healthy Volunteers Effects Of Different Doses Of Rtms On Trmentioning
confidence: 99%
“…However, a single session of ECT does not increase CSP 23 while several ECT increase CSP (24), a finding consistent with GABAergic activity of ECT. Transcranial magnetic stimulation also increases the CSP and depressed patients who responded to the high frequency rTMS (20Hz) of the left DLPFC have an increase of CSP and ICI [25][26][27]. Change of ICI was correlated with improved HAM-D score (Hamilton Rating Scale for Depression) [28].…”
Section: Discussionmentioning
confidence: 98%